GEOMETRIC THINKING OF JUNIOR HIGH SCHOOL STUDENTS IN SOLVING SIMILARITY PROBLEMS BASED ON GENDER DIFFERENCES - Sartika Tempola; Dwi Juniati; Siti Khabibah (EMTEKA: Jurnal Pendidikan Matematika, 2026)
This study aims to describe students’ geometric thinking processes in solving similarity problems based on gender differences using Polya’s problem-solving stages. This study was motivated by students’ difficulties in understanding geometric concepts and the lack of in-depth analysis of thinking processes in previous studies. A qualitative descriptive approach was employed with two ninth-grade students (one male and one female) selected purposively based on equivalent mathematical ability. Data were collected through Geometry Problem-Solving Tasks (GPST) and semi-structured interviews. Data were analyzed through reduction, display, and conclusion drawing, supported by triangulation techniques. The results indicate that female students demonstrate more systematic and reflective thinking, while male students show more flexible and intuitive strategies. These findings highlight that gender differences influence cognitive processes rather than final outcomes. The study contributes to a deeper understanding of students’ geometric thinking using Polya’s framework. Penelitian ini bertujuan untuk mendeskripsikan proses berpikir geometris siswa dalam menyelesaikan masalah kesamaan berdasarkan perbedaan gender menggunakan tahapan pemecahan masalah Polya. Pendekatan deskriptif kualitatif digunakan. Subjek penelitian adalah dua siswa SMP dengan kemampuan matematika yang setara. Data dikumpulkan melalui tugas pemecahan masalah dan wawancara semi-terstruktur. Data dianalisis menggunakan reduksi, tampilan, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa siswa perempuan cenderung lebih sistematis dan reflektif, sedangkan siswa laki-laki cenderung lebih fleksibel tetapi kurang terstruktur. Namun, keduanya mencapai solusi yang benar. Temuan ini menunjukkan bahwa perbedaan gender memengaruhi proses kognitif daripada hasil belajar.